2013
DOI: 10.1111/ijs.12135
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Benefits of Mindfulness-Based Interventions following Transient Ischemic Attack and Stroke

Abstract: Following transient ischemic attack/stroke, people may derive a range of benefits from mindfulness-based interventions; however, further methodologically robust trials are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 46 publications
(107 reference statements)
1
91
0
5
Order By: Relevance
“…Recent meta-analyses have established MBSR as efficacious in improving mental health outcomes in cancer [1416]. Systematic reviews in adults with cancer [17,18,15] and in non-cancer populations [19,20] have concluded that mindfulness-based interventions are promising but require further investigation, particularly with respect to treating fatigue and its correlates [1,21]. Although clinical practice guidelines added MBSR as an evidence-based intervention for fatigue following cancer treatment in 2014 [10], to date only trials comparing MBSR to wait-list controls on fatigue outcomes have been conducted [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses have established MBSR as efficacious in improving mental health outcomes in cancer [1416]. Systematic reviews in adults with cancer [17,18,15] and in non-cancer populations [19,20] have concluded that mindfulness-based interventions are promising but require further investigation, particularly with respect to treating fatigue and its correlates [1,21]. Although clinical practice guidelines added MBSR as an evidence-based intervention for fatigue following cancer treatment in 2014 [10], to date only trials comparing MBSR to wait-list controls on fatigue outcomes have been conducted [1113].…”
Section: Introductionmentioning
confidence: 99%
“…MM has also been successfully applied to clinical populations dealing with similar symptoms. An RCT demonstrated positive benefits of meditation in persons with multiple sclerosis (Grossman, et al, 2010), and studies with less rigorous methodologies have shown benefits of meditation in traumatic brain injury (Bedard et al, 2012; Johansson, Bjuhr, & Ronnback, 2012) and stroke (Johansson, et al, 2012; Lawrence, Booth, Mercer, & Crawford, 2013). MM training has also been explored in people with aphasia resulting in improved reaction times in a cognitive task (Orenstein, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…et al в своих статьях говорят о необходимости как предоставления информации о забо-левании квалифицированными медицинскими работника-ми, так и поддержки со стороны медицинского персонала и семьи, что будет способствовать повышению привержен-ности лечебным мероприятиям и вторичной профилакти-ке инсульта [33][34][35]. Ранее Lawrence M. et al провели исследование, которое показало положительное влияние мероприятий, основанных на осознанных действиях паци-ента, на целый ряд психологических, физиологических и психосоциальных последствий ТИА, таких как тревога, депрессия, умственная усталость, артериальное давление, неадекватное восприятие здоровья и качества жизни [34]. Мотивация пациентов очень важна, так как есть исследова-ния (Hilldson et al), которые отражают недооценку пациен-тами, перенесшими ТИА, тяжести их заболевания [36].…”
Section: медицинская реабилитацияunclassified